Catch-up Basic Immunization Education for Children with Delayed Immunization: Implementation in Children Aged ≥ 9 Months: Edukasi Imunisasi Dasar Anak yang Tertunda: Imunisasi Kejar pada Anak Usia ≥ 9 Bulan - Ivana Devitasari; Neneng Safitri; Bella; Nita Kusuma; Lidia Widia (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Immunization is one of the most effective health interventions to reduce morbidity, disability, and mortality caused by vaccine-preventable diseases (VPDs). However, in practice, many children still experience delays in receiving basic immunizations, including those in Samba Danum Village, Central Katingan District. This community service activity aimed to improve parents’ knowledge about basic immunization and to conduct catch-up immunization for children aged ≥ 9 months who had not received immunizations according to schedule. The implementation method consisted of preparation, education through interactive lectures and discussions, catch-up immunization in collaboration with health workers, and evaluation using pre-test and post-test. The results showed a significant increase in parents’ knowledge, with higher average post-test scores compared to pre-test. In addition, catch-up immunization coverage reached more than 80% of the target group. This activity demonstrated that proper education and accessible health services can enhance community awareness and improve basic immunization coverage. In the future, similar activities are expected to be expanded to other areas with similar conditions, accompanied by continuous monitoring to ensure the sustainability of the immunization program.